Cinzas do Brasil: esmaltes cerâmicos do bagaço de cana-de-açúcar - Murakawa, Vanessa Yoshimi [UNESP] (2013)
The use of plant ashes in ceramic glazes comes from ancient time. Originated in the East, this technique has been used by several contemporary ceramists in Brazil and stands out as an aid to sustainable development, as it works with reuse of materials. Throught the fire, dry leaves, grass cuttings and waste organic material can be turned into ashes and used in the composition of these glazes. This research aims to continue the study related to the use of plant ashes in the composition of ceramic glazes, investigating in particular the ash from the sugarcane bagasse. Also, aims to research the possibilities of glazing through trials with sugarcane bagasse ashes from a power plant in different clays and firing kilns, as well as a the historical production of ceramics in Eastern coutries (China, Korea and Japan), where the technique was initiated and developed, until the potters that use this unameling technique in Brazil.